Opposites attract - the oxymoron / Afni Anida Adnan, Angeline Ranjethamoney Vijayarajoo (AP, Dr.) and Sharina Salmi Azmi - Adnan, Afni Anida; Vijayarajoo, Angeline Ranjethamoney; Azmi, Sharina Salmi (Universiti Teknologi MARA, Negeri Sembilan, 2023)
It is said that ‘opposites attract’, and in the field of Linguistics, nothing can be truer of this than the fact that oxymorons exist. What is an oxymoron? The word oxymoron is ‘a literary device that juxtaposes contradictory terms’ (Ellis, 2022). Put simply, an oxymoron is a combination of words that carry meaning which would otherwise be antonyms or words that mean the opposites of each other. What is even more interesting is that the word oxymoron is in itself an oxymoron. According to Shew (2022), the word oxymoron comes from the Greek words oksús (meaning “keen”) [or oxys (“sharp”) (Masterclass, 2022)] and mōros (meaning “stupid”), leading to the phrase “sharp stupid”. There are many possible reasons behind the existence, formation, and use of the oxymoron. The oxymoron, particularly those in the English Language, exist because the language is arbitrary, with an infinite ability to form new words. It is interesting to note that though at a glance, oxymorons may be formed by combining any two parts of speech, they are in actual fact, mostly formed by an adjective + noun combination, or adverb + adjective combination. This is because a noun + noun combination will most certainly equate to a compound noun and not an oxymoron (flower + pot, hand + bag).